AB0688 Treatment with Rituximab in Systemic Sclerosis Patients: Our Experience in a Pilot Clinical Trial. (9th June 2015) - Giuggioli, D.; Lumetti, F.; Colaci, M.; Cassone, G.; Cestelli, V.; Ferri, C.
Abstract : Background: Systemic sclerosis (SSc) is an immune-mediated disorder characterized by abnormal fibrosis and diffuse microangiopathy with skin and internal organ involvement due to both T- and B-lymphocyte activation. The present study aimed to assess the efficacy of long-term treatment with rituximab (RTX), a chimeric monoclonal antibody that targets B-cell CD20. The rationale for the use of RTX in SSc is based on experimental data suggesting a key role for B cells in regulating the fibrotic process. Objectives: The present study aimed to assess the efficacy of long-term treatment with rituximab (RTX) in systemic sclerosis patients. Methods: Eleven SSc patients (M/F 3/8, mean age 43.2±10.5SD years, mean disease duration 3.6±6.2SD years) underwent to RTX cycle (weekly infusion of RTX 375 mg/m 2 of body surface plus 100 mg methylprednisolone for 4 weeks); in 10/11 RTX was repeated every 6 months for a total of 2-6 cycles. Patients' clinical-serological evaluation, including HAQ assessment and visual analogical scale (VAS), was performed every six months. Results: At the end of the follow-up period (3.7±2.8 SD years) an improvement of the skin sclerosis involvement was constantly observed; in particular, patients with diffuse SSc cutaneous variant showed a significant decrease of modified Rodnan skin score (from 25±4.1 to 17.2±4.1; p<0.004). Similarly, the articular involvement, melanodermia, and calcinosis ameliorated if compared to baseline; these positive clinical variations were mirrored by a subjective recovery of patients' well being in all cases (HAQ, VAS). No significant variations were observed with regards to other SSc clinical manifestations; in particular, lung involvement remained stable or showed a moderate progression at the last patients' evaluation. Finally, in no cases significant side effects were observed. Conclusions: Our results indicate that treatment of SSc patients with RTX may be particularly effective for severe skin sclerosis, as suggested by other preliminary trials. The scarce efficacy of RTX on some disease manifestations may suggest the use of combined treatment, namely RTX with other antifibrotic/vasoactive drugs. Disclosure of Interest: None declared